Wolf space use during denning season on Prince of Wales Island, Alaska. Issue 1 (18th December 2018) - Roffler, Gretchen H.; Gregovich, David P.
Abstract : Wolf Canis lupus reproductive success may be enhanced by access to favorable habitat with limited disturbance during denning season. Therefore, protection of den sites can be an important management strategy for maintaining viable wolf populations. On Prince of Wales Island in southeast Alaska, USA, management agencies recommend protection of dens and surrounding home ranges. However, these agencies are concerned current protection buffer sizes might be inadequate to promote pup‐rearing success. To inform management decisions regarding buffers surrounding wolf dens, we used wolf GPS collar data during 2012–2016 to quantify core and home range area sizes during denning season. We used an autocorrelated kernel density estimator (AKDE) to calculate the extent of home ranges and fit individual wolf movement models. Breeding wolves used smaller core (AKDE 50% isopleth = 6 km2, SD = 4 km2) and home range areas (AKDE 95% isopleth = 57 km2, SD = 17 km2) during denning season (15 April–15 June) than non‐breeding wolves at active dens (core = 69 km2, SD = 45 km2; home range = 252 km2, SD = 161 km2). Home ranges for breeding wolves and wolves belonging to a reproductive pack were smaller than non‐breeding wolves throughout the pup‐rearing period (15 April–31 July). The mean minimum and maximum distance from the core area edge to the active den site (1186–6326 m) varied widely but was smaller for breeding wolves (734–2308 m), and all distances exceeded the existing recommended den buffer distance (366 m). These results underscore the importance of evaluating individual variation in space use when considering management actions intended to protect cooperative breeders or other social carnivores. Wolf managers should recognize the current protection buffer around dens constitutes only a portion of the core area used by breeding wolves, and habitat alterations near den sites may force breeding wolves to use sub‐optimal habitat they would normally avoid.